Marketing and Advertising Ethical Stance toward Customers - A. Alsheeha, Sarah (British Journal of Marketing Studies, 2018)
Marketing ethics is a well-established area of marketing research. Following the marketing ethics is important and a key factor for a firm to survive and succeed.  Research has shown that it is critical to focus on the accuracy of promotional messages provided to the customers. Giving the customer inaccurate information is known as misleading advertisements. This action is unethical due to leading the customer to buy a product which the customer thinks like what has been sawed in the Ad. Unfortunately, unethical advertisements are not directed just towered adult, however, children involved too. Moreover, many studies state that there is a growing number of marketers who are attracting the customers to buy unneeded products by using psychological and emotional appeals. I believe these appeals are the driving force would excite quick responses from the customers.  This study aims to identify marketing ethics by reviewing past studies and discover some unethical practices in marketing.